STUDENT’S DIFFICULTIES ON WRITING DESCRIPTIVE TEXT - Sholihatul Hamidah Daulay; Emeliya Sukma Dara Damanik; Nuriza Annisa (Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This research investigates an overview of students' difficulties in writing descriptive text through linguistic and psychology problems. This research presents a case study as qualitative research of students in eighth grade of SMP Darussalam Medan. The sample comprised 10 students (4 males and 6 females) through purposive sampling. This study used observation, documentation, and interview. In this study, data collection from each instrument was as follows: document data collection through student descriptive writing and direct interview data collection via video call on WhatsApp. The data analysis procedure of this study was followed by Miles and Hubermen in 1984 which covered data reduction, data interpretation, and drawing a conclusion. Based on the observation result supported by the document and interview through the triangulation method, students found difficulties in using punctuation and capitalization in writing descriptive. The students’ felt difficulty in using grammar lack of vocabulary and mechanics. In addition, the practice of writing essays also makes students skilled in writing. With practice, students will know the difficulties they face in writing to know the quality of their writing. Keywords: Difficulties, Writing skill, Descriptive text.